Crecimiento del híbrido de tilapia roja oreochromis sp con agua de pozo a diferentes densidades - Sanginéz Romero, Rosendo Kleber (2007)
The present work made it to him in the camaronera “Marieliza” of property of the Mr. Ing. Luís Matute, located in the Parish Pálmales, canton Arenillas, County of The Gold. This work had duration of three months (October-December 2005). This investigation was carried out it in a pool that has an area of 5000 m2.Los alevines that you/they were used they were acquired through the Company Aquarius. The siembra density was of 100, 200 and 300 tilapias for cage. The tilapias was fed with having balanced initially of 35%, then he/she decreased the protein percentage at the 28% extrusado, they were fed three up-to-date times (6:30, 12:30 and 18:30). The statistical analysis for increment of weight demonstrates that if there was significant difference you enter the three densities. The density that I present the best survival was of 200 fish-cage he/she obtained 98,5% of survival at the end of the work, followed by the density of 300 fish-cage 97,8% and the density of 300 fish-cage with 97,7%. The best conversion feeding was that of 300 fish-cage with 1,44, followed by the density of 200 fish-cage with 1,29 and finally the density of 100 fish-cage with 1,24.